Performance management in context: formative cross-functional performance monitoring for improvement and the mediating role of relational coordination in hospitals. Issue 3 (4th February 2019) - McDermott, Aoife M.; Conway, Edel; Cafferkey, Kenneth; Bosak, Janine; Flood, Patrick C.
Abstract: Recent research suggests that to fully realise its potential, performance management should be bespoke to the social context in which it operates. Here, we analyse factors supporting the use of performance data for improvement. The study purposively examines a developmentally oriented performance management system with cross-functional goals. We suggest that these system characteristics are significant in interdependent work contexts, such as health care. We propose and test that (a) relational coordination helps employees work effectively to resolve issues identified through formative and cross-functional performance monitoring and (b) that this contributes to better outcomes for both employees and patients. Based on survey data from management and employee representatives across Irish acute hospitals, the study found that perceptions of relational coordination mediated the link between formative cross-functional performance monitoring and employee outcomes and partially mediated the link between formative cross-functional performance monitoring and patient care. Our findings signal potential for a more contextually driven and interdependent approach to the alignment of management and human resource management practices. While relational coordination is important in health care, we also note potential to identify other social drivers supporting productive responses to performance monitoring in different contexts.